Workplace Diversity and Employee Performance in Nepalese Commercial Banks - Rana, Srijana (Nepalese Journal of Management, 2025)
This study examines the workplace diversity and employee performance in Nepalese commercial banks. Employee performance is the dependent variable. Similarly, the selected independent variables are age diversity, gender diversity, ethnic diversity, education diversity and workplace culture. The primary sources of data are used to assess the opinions of respondents regarding age diversity, gender diversity, ethnic diversity, education diversity, workplace culture, and employee performance. The study is based on the primary data of 133 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of workplace diversity and employee performance in Nepalese commercial banks. The study showed a positive impact of age diversity on employee performance. It indicates that organization having employee from diverse age group leads to increase in employee performance. Similarly, the study showed a positive impact of gender diversity on employee performance. It indicates that gender diversity leads to increase in employee performance. Likewise, the study showed a positive impact of ethnic diversity on employee performance. It indicates that firm having employee of different racial and ethnic background leads to increase in employee performance. Further, the study also showed a positive impact of education diversity on employee performance. It indicates that employee from different educational background leads to increase in employee performance. In addition, the study showed a positive impact of workplace culture on employee performance. It indicates that diversified workplace culture leads to increase in employee performance.